2007
DOI: 10.1161/01.str.0000252129.18605.c8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Matrix Metalloproteinase-2 and -9 Promote the Progression of Cerebral Aneurysms in Rats

Abstract: Background and Purpose-Mechanisms of initiation, progression and rupture of cerebral aneurysms have not yet been fully understood despite its clinical significance. Matrix metalloproteinases (MMPs) are a family of proteinases which are involved in the remodeling of vascular walls. In the present study, we investigated the significance of MMPs in the progression of cerebral aneurysms. Methods-Cerebral aneurysms were experimentally induced in 7-week-old male Sprague-Dawley rats. MMP-2 and MMP-9 expression was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
267
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(287 citation statements)
references
References 24 publications
15
267
2
3
Order By: Relevance
“…15 This may, in part, explain how inflammatory cells and cytokines promote vascular wall remodeling and aneurysm formation. 28,30 In summary, results of the present studies provide novel in vitro and in vivo evidence showing that TNF-a profoundly suppresses expression of SMC differentiation genes and myocardin while concomitantly activating expression of KLF4 and matrix remodeling/inflammatory genes. Although phenotypic modulation cannot be directly tested in cerebral aneurysms as carried out in cultured SMCs and rat carotid arteries-a model of intracranial atherosclerosis 20,21 -TNF-a was increased early in an animal model of aneurysm formation in parallel with changes in expression of the SMC marker gene SM-a-actin, SM-MHC, KLF4, and proinflammatory/matrix-remodeling genes in a similar fashion.…”
Section: Discussionmentioning
confidence: 60%
“…15 This may, in part, explain how inflammatory cells and cytokines promote vascular wall remodeling and aneurysm formation. 28,30 In summary, results of the present studies provide novel in vitro and in vivo evidence showing that TNF-a profoundly suppresses expression of SMC differentiation genes and myocardin while concomitantly activating expression of KLF4 and matrix remodeling/inflammatory genes. Although phenotypic modulation cannot be directly tested in cerebral aneurysms as carried out in cultured SMCs and rat carotid arteries-a model of intracranial atherosclerosis 20,21 -TNF-a was increased early in an animal model of aneurysm formation in parallel with changes in expression of the SMC marker gene SM-a-actin, SM-MHC, KLF4, and proinflammatory/matrix-remodeling genes in a similar fashion.…”
Section: Discussionmentioning
confidence: 60%
“…Macrophage infiltration and activation play key roles in prolonged inflammation and are associated with the growth of IAs 9. As shown in Figure 2A, Iba1‐positive macrophages had less infiltration into the IAs of the anagliptin‐treated group than those in the vehicle group (Figure 2A).…”
Section: Resultsmentioning
confidence: 92%
“…Chronic inflammation involves the infiltration of monocytes/macrophages11 and the subsequent release of proinflammatory cytokines, chemokines,11 and matrix‐degrading proteinases, such as matrix metalloproteinases,9 that induce cell death and the destruction of the extracellular matrix, causing the thinning of the aneurysmal wall. Inhibiting NF‐κB and ETS‐1 (E26 transformation–specific sequence 1) with chimeric decoy oligodeoxynucleotides decreases expression of MCP‐1 and macrophage infiltration in rat IA models,12 indicating that inflammatory processes play a crucial role in the formation and growth of IAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also concluded that the decrease in media thinning results from mast cells' modulation of MPP-2 and MMP-9 expression. [17,19] Overall, these data suggest that the degranulation of mast cells plays a role in IA formation.…”
Section: Mediators Of Inflammationmentioning
confidence: 65%